Management of patients after their first myocardial infarction. - Flapan, A. D. (BMJ Group, 1994)
In the past 20 years there has been a steady improvement in the short term prognosis of patients with myocardial infarction, following the introduction of beta blockers, thrombolysis, and aspirin. Patients treated with thrombolytic drugs have a lower overall mortality after myocardial infarction but remain at risk of non-fatal reinfarction or death, and in one study almost half of all survivors of acute myocardial infarction died or suffered a further ischaemic event within three years. It is therefore important to have a strategy to identify patients at high risk, to reduce the subsequent development of cardiac failure and mortality, and to have effective measures for secondary prevention to reduce the incidence of reinfarction as well as to promote rehabilitation.